THE EFFECT OF HOUSEKEEPING PERFORMANCE ON GUEST SATISFACTION AT GRAND ROCKY HOTEL BUKITTINGGI - Yoga Dwi Putra (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to examine the effect of housekeeping service performance on guest satisfaction at the Grand Rocky Hotel in Bukittinggi. A quantitative approach using an associative method was employed, involving 100 respondents selected through incidental sampling from guests staying at the hotel between August 2025 and January 2026. Data were collected using a validated and reliable questionnaire and analyzed using descriptive statistics, the Respondent Achievement Level (RAL), simple linear regression, the coefficient of determination (R²), and the t-test using IBM SPSS Version 25. The results of the study indicate that housekeeping performance has a positive and significant effect on guest satisfaction, as shown by the regression equation Y = 9.894 + 0.503X, an F-value of 77.398, and a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.441 indicates that housekeeping performance explains 44.1% of the variance in guest satisfaction, while the remaining 55.9% is influenced by other factors. These findings suggest that maintaining and improving the quality of housekeeping performance can be an effective strategy for enhancing guest satisfaction and loyalty.